PENGARUH DIVERSIFIKASI PRODUK TERHADAP PENJUALAN (Studi Kasus pada Perusahaan Konveksi “Faiza Bordir” Bangil – Pasuruan) - Shofwan Khamidi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This type of research is descriptive research with a case study approach, in which researchers attempted to describe and depict the object studied by the state as it is to perform calculations and draw conclusions. The data analysis technique used is the Mean Growth analysis, method of least squares, simple correlation and multiple linear regression. Growth analysis based on known Mean average sales volume growth and earnings before diversifying product amounted to 2.21% and 1.51%, after an average product diversification and earnings growth in sales volume increased by 3.71% and 4.57% . Trend analysis results with the Least Square method for total sales are projected to increase. Correlation coefficient between volume and sales turnover by diversifying their products, namely: to mukenah of 0.798 and 0.858, 0.808 and 0.885 for Kebaya, Clothing at 0.839 and 0.958 Adult, Children Clothing 0.876 and 0.971, 0.614 for Adult Shirt and 0,810, Long Dress of 0.965 and 0.981, Embroidered Shoes at 0.835 and 0.972. Results of multiple linear regression analysis note that the diversification effect on sales volume, indicated by the F-calculated value of 18.662 and adjusted R2 value of 0.848 where sig. <0.05. ¬ So is the sales turnover, that product diversification effect on sales turnover, indicated by the F-calculated value of 5868.751 and adjusted R2 value of 0.999 where sig. <0.05 This suggests that the relationship between product diversification and the effect on sales is strong. Keywords : Product Diversifcation, sale